PHBS: PENDIDIKAN KESEHATAN REPRODUKSI SEBAGAI UPAYA PREVENTIF BAGI SISWA SEKOLAH DASAR DI DESA BUDAYA SUNGAI BAWANG - Maria Floriana Ping; Fransiska Novita Sari (Jurnal Pengabdiaan Masyarakat Kasih (JPMK), 2023)
Early adolescence is a critical period of physical maturation often accompanied by risky behaviors due to a lack of reproductive health knowledge. This community service project aims to enhance the understanding of elementary school students regarding reproductive health and Clean and Healthy Living Behavior (PHBS). The activities were conducted at SD Negeri 014 in Sungai Bawang Cultural Village, involving 30 students from the 5th and 6th grades. The implementation method included interactive education using flip charts and role-play media, as well as evaluation through pre-test and post-test questionnaires. The results showed a significant increase in students' knowledge levels, with the mean score rising from 22.42 to 33.23 after the intervention (p=0.00). This improvement proves that school-based education is effective in equipping students to face puberty. In conclusion, reproductive health education integrated with PHBS can serve as an effective preventive strategy for school-aged children in fostering independence in maintaining personal health and protection from social risks.